2018
DOI: 10.1021/acs.jpcc.8b00597
|View full text |Cite
|
Sign up to set email alerts
|

Small Carbon Nano-Onions: An Ion Mobility Mass Spectrometric Study

Abstract: Structures and charges of nanocarbon cluster ions, C n z+ (100 ≤ n ≤ 800, z = 1 and 2), have been determined using ion mobility mass spectrometry. For singly charged ions, a compact cluster ion series was observed in addition to monolayer fullerene ions for n = 260−700 continuously. Previous electron microscopic observations indicated that the compact clusters were bilayer fullerenes (nano-onions), in which the inner and outer layers grow from a structure close to [C 30 @C 230 ] + at n = 260. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…On the other hand, the two series of Mg n O n + and Mg n O n –1 + were mainly observed in the mass spectrum at E inj = 250 eV (Figure c). The one oxygen-rich and one oxygen-poor series were clearly distinguished in this size range up to n = 27 ( m / z ≈ 1080) because the resolving power between Mg n O n +1 + and Mg n +1 O n + , up to 1080/8 ≈ 140, is much smaller than the mass resolution of the apparatus, m /Δ m ≈ 230 . The Mg n O n + and Mg n O n –1 + series were also observed in previous mass spectroscopic studies. As the injection energy increases, collision-induced dissociation (CID) is likely to occur more efficiently at the entrance of the cell.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…On the other hand, the two series of Mg n O n + and Mg n O n –1 + were mainly observed in the mass spectrum at E inj = 250 eV (Figure c). The one oxygen-rich and one oxygen-poor series were clearly distinguished in this size range up to n = 27 ( m / z ≈ 1080) because the resolving power between Mg n O n +1 + and Mg n +1 O n + , up to 1080/8 ≈ 140, is much smaller than the mass resolution of the apparatus, m /Δ m ≈ 230 . The Mg n O n + and Mg n O n –1 + series were also observed in previous mass spectroscopic studies. As the injection energy increases, collision-induced dissociation (CID) is likely to occur more efficiently at the entrance of the cell.…”
Section: Resultssupporting
confidence: 55%
“…The one oxygen-rich and one oxygen-poor series were clearly distinguished in this size range up to n = 27 (m/z ≈ 1080) because the resolving power between Mg n O n+1 + and Mg n+1 O n + , up to 1080/8 ≈ 140, is much smaller than the mass resolution of the apparatus, m/Δm ≈ 230. 41 + , which contains one more Mg atom than the latter magic number composition, was extremely low in Figure 1c. This feature was also observed in previous mass spectrometric studies.…”
Section: Resultsmentioning
confidence: 94%
“…The experimental CCSs of the observed ions were calculated from the measured arrival time by using eqs –. In the present ion mobility measurements, the E / N value is 7.5–9.1 Td (1 Td = 10 –17 V cm 2 ), which is similar to or less than that used in our previous IMMS studies and is considered to be low enough so that the drifting ions can be regarded as thermalized.…”
Section: Methodsmentioning
confidence: 63%
“…Apart from C 60 , larger carbon clusters ranging in size up to C 240 formed upon laser vaporization of graphite in a continuous flow of helium have also been investigated by IMS and results interpreted in terms of closed shell fullerene cage structures. 32 Recently Misaizu et al 33 have used IMS to study even larger carbon clusters formed in this way. They showed that apart from single-shelled cages, double-shelled fullerene onion cages begin to be observed starting at roughly C 260…”
Section: Introductionmentioning
confidence: 99%